Religion, the enlightenment, and the new global order - Owen, John M. (John Malloy), 1962-; Owen, J. Judd (New York : Columbia University Press, 2010)
Largely due to the cultural and political shift of the Enlightenment, Western societies in the eighteenth century emerged from sectarian conflict and embraced a more religiously moderate path. In nine original essays, leading scholars ask whether exporting the Enlightenment solution is possible, or even desirable, today. Contributors begin by revisiting the Enlightenment's restructuring of the West, examining its ongoing encounters with Protestant and Catholic Christianity, Judaism, Islam, and Hinduism. While acknowledging the necessity of the Enlightenment emphasis on toleration and peaceful religious coexistence, these scholars nevertheless have grave misgivings about the Enlightenment's spiritually thin secularism. The authors ultimately upend both the claim that the West's experience offers a ready-made template for the world to follow and the belief that the West's achievements are to be ignored, despised, or discarded.
I. The Enlightenment revisited : theoretical questions. Religion, the Enlightenment, and the new global order / John M Owen IV and J. Judd Owen -- Religious violence or religious pluralism : the essential choice / William A. Galston -- Religion, Enlightenment, and a common good / Jean Bethke Elshtain -- How and why the West has lost confidence in its foundational political principles / Thomas L. Pangle -- II. The Enlightenment, secularity, and the religions. The Enlightenment project, Spinoza, and the Jews / David Novak -- Puritan sources of Enlightenment liberty / John Witte Jr. -- India : the politics of religious reform and conflict / Pratap Bhanu Mehta -- Reason and revelation in Islamic political ethics / Abdulaziz Sachedina -- Islam, constitutionalism, and liberal democracy / Sohail H. Hashmi -- The identity of the Christian Democratic Movement and theory of democracy / Roberto Papini -- Concluding thoughts / John M. Owen IV and J. Judd Owen.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Religion and politics; Enlightenment; Islam; Islam; Religion et politique; Siècle des Lumières.; Islam; Islam; Enlightenment (18th-century western movement); RELIGION -- Comparative Religion; BODY, MIND & SPIRIT -- Gaia & Earth Energies; RELIGION -- Christianity -- General; Enlightenment; Islam; Religion and politics